Evaluation of haptoglobin concentration in clinically healthy dairy cows: correlation between serum and milk levels - Ramiro Fouz; Ruth Rodríguez-Bermúdez; Iris J. Rodríguez-Godina; María Rodríguez-Domínguez; Margarita Rico; Francisco J. Diéguez (Journal of Applied Animal Research)
The study aimed to analyse serum haptoglobin concentrations by calving number and lactation phase in clinically healthy dairy cattle and to determine the correlation between concentrations in serum and milk samples. For this purpose, serum samples were collected from 228 clinically healthy cows after milking from 14 randomly selected herds. Additionally, milk samples were collected from 80 out of the 228 cows from the milking prior to blood collection. Both serum and milk samples were analysed with a commercial ELISA test. The effect of the calving number and lactation phase on mean serum haptoglobin concentrations was examined by Kruskal–Wallis/Jonckheere–Terpstra tests. After that, in a multivariate approach, a mixed-effects linear model was also performed. In addition, intraclass correlation coefficients were used to evaluate the correlation between concentrations in serum and milk samples. Results indicated a downward trend in haptoglobin concentrations throughout lactation, that was statistically significant when comparing fresh cows with the remaining lactation phases. The higher haptoglobin concentrations in fresh cows could be the result of inflammatory illnesses without clinical disease, stress or variations within the physiological state. Although previous studies showed some discrepancies, a good correlation between serum and milk concentrations has been observed in the present paper.